Dietary Diversity Choices of Women: Evidence from Cassava Farming Households in Nigeria - Oluwaseun A. Otekunrin; Olutosin A. Otekunrin (Archives of Current Research International, 2021)
In this study, we examined dietary diversity of women in cassava farming households of South-West, Nigeria. Multi-stage sampling procedure was used to collect data on 352 farming households comprising 212 women members (158 women of child-bearing age (20-49 years) and 54 women above 49 years) between December 2019 and March 2020 in Oyo and Ogun States of South-West, Nigeria. The Minimum Dietary Diversity for Women (MDD-W) questionnaire was adapted and used to obtain the dietary diversity scores (DDS) of women of child bearing age over a 24-hour recall period. The individual version of the Household dietary diversity questionnaire was adapted and used to obtain the DDS of women above 49 years. Separate logistic regression models were fitted to determine the influence of selected variables on the dietary diversity of the two categories of women. Our results show that more than half of the women (55.1%) in the child-bearing category (20-49 years) did not attain the minimum score of 5 out of 10 food groups. In the older women category (> 49 years), more than half of the women (68.5%) met the required 4 or more food groups. In the child-bearing age category, the odds of attaining the minimum dietary diversity level were 0.04% smaller with an additional increase in transport cost. Also, women who had female household heads were approximately three times more likely to attain the minimum dietary diversity level than women who did not have female household heads. In the older women category, the odds of attaining the minimum dietary diversity level were 98.9% smaller for women with good road condition than for women with poor road condition. These results are useful for evidence-based decision making that can have positive impact on the lives of women in cassava farming households.